Second allogeneic stem cell transplantation in patients with acute lymphoblastic leukaemia: a study on behalf of the Acute Leukaemia Working Party of the European Society for Blood and Marrow Transplantation - Nagler, Arnon; Labopin, Myriam; Dholaria, Bhagirathbhai; Finke, Jürgen; Brecht, Arne; Schanz, Urs; Niittyvuopio, Riitta; Neubauer, Andreas; Bornhäuser, Martin; Santarone, Stella; Beelen, Dietrich; Shimoni, Avichai; et al. (British Journal of Haematology, 2019)
Although second allogeneic haematopoietic cell transplantation (allo-HCT2) is a therapeutic option for patients relapsing after first HCT (allo-HCT1), there is limited data on allo-HCT2 in patients with acute lymphoblastic leukaemia (ALL). We retrospectively studied 245 patients receiving allo-HCT2 as a salvage treatment for relapse following allo-HCT1 between the 2000 and 2017. The median age at allo-HCT2 was 34·6 years (range: 18-74). One hundred and one patients (41%) received sibling donor and 144 (59%) unrelated donor allo-HCT2. Acute graft-versus-host disease (GVHD) grade II-IV and III-IV occurred in 33% and 17% of the patients, respectively. The incidence of 2-year total and extensive chronic GVHD was 38% and 19%, respectively. The 2- and 5-year cumulative incidence of non-relapse mortality, relapse incidence, leukaemia-free survival, overall survival and GVHD-free, relapse-free survival (GRFS) were 24% and 26%, 56% and 62%, 20% and 12%, 30% and 14% and 12% & 7%, respectively. In multivariate analysis, factors associated with overall survival were age, time from allo-HCT1 to relapse, conditioning for allo-HCT1, Karnofsky score at allo-HCT2 and donor type for allo-HCT2. In conclusion, outcomes of allo-HCT2 in ALL patients were poor, with only 14% overall survival and 7% GRFS at 5 years with very high relapse incidence.
EVALuna2:184253